Wage curve: An application for the case of Mexico, 1993-2002 - Castro Lugo, David (Estudios Económicos de El Colegio de México, 2006)
The purpose of this document is to analyze the relation between unemployment and wages in Mexico during the 1993-2002 period, using the methodology of wage curve. The results show a negative relation between the rate of local unemployment and the wages, although its elasticity is inferior to the obtained in other countries. The classification of the workers by groups establishes that the conditions of local unemployment do not affect the remunerations of workers of the public sector. In addition, there exists different wage elasticity between different groups (sex, disposition of social benefits, age and schooling). The exploration of alternative specifications indicates that wages have a different behavior based on the level from the rate of leisure.